A Case Report and Review of Literature: Epithelioid Hemangioendothelioma—An Uncommon Challenging Case - Soni, Sweta; Devnani, Bharti; Elhence, Poonam; Soni, Kapil; Vedant, Deepak; Gupta, Palak; Pareek, Puneet; Vyas, Rakesh Kumar (Indian Journal of Medical and Paediatric Oncology, 2023)
Introduction Epithelioid hemangioendothelioma (EHE) is a rare vascular tumor of soft tissue and bone that may uncommonly occur in the liver, lung, and head and neck region. EHEs have a higher predilection for recurrence at the local site as well as distant metastasis. Surgical excision is important and is the treatment in localized diseases. A decision to give adjuvant radiotherapy should be subjective and may differ on case-to-case basis. Limited studies are available exploring the role of targeted or systemic therapy.Case Presentation A 56-year-old lady represented with right-sided submandibular region EHE with bilateral lung metastasis. The patient underwent surgery and radiotherapy followed by targeted therapy tab pazopanib for systemic control. At 2 years of follow-up, positron emission tomography-computed tomography showed local regional control and stable systemic diseases.Conclusion The uncertainty in choosing the most suitable treatment of EHE patients is high and may result in dissatisfactory outcomes among several patients. The present case study identified a treatment dilemma making management more challenging for rare EHE with mandibular involvement.
Keywords: hemangioendothelioma; surgery; radiotherapy; pazopanib; outcomes; case report